2007
DOI: 10.1007/s00253-007-1126-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect on epidermal cell of soybean protein-degraded products and structural determination of the root hair promoting peptide

Abstract: Peptide(s) produced from degraded soybean protein by an alkaline protease from Bacillus circulans HA12 (degraded soybean-meal products; DSP) increased the number of both the root hair cells (trichoblasts) and hairless cells (atrichoblasts) of Brassica rapa by about 4.4 times and 1.9 times, respectively. To identify the root hair-promoting peptide(s) in DSP, the origin protein of the root hair-promoting peptide(s) was identified as Kunitz trypsin inhibitor (KTI). The root hair-promoting peptide in the degraded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Root hair promoting effect of degraded soybean meal products (DSP). A: root of Brassica rapa grown in plant growth medium (Matsumiya et al, 2007), B: root of B. rapa grown with DSP in plant growth medium. Bar denotes 1 mm.…”
Section: Effect Of Dsp On Root Hair Promotionmentioning
confidence: 99%
See 2 more Smart Citations
“…Root hair promoting effect of degraded soybean meal products (DSP). A: root of Brassica rapa grown in plant growth medium (Matsumiya et al, 2007), B: root of B. rapa grown with DSP in plant growth medium. Bar denotes 1 mm.…”
Section: Effect Of Dsp On Root Hair Promotionmentioning
confidence: 99%
“…Activates the synthesis of proteinase inhibitors (McGurl, et al, 1992) RHPP Root hair promotion Adventitious root formation GGIRAAPTGNER (Matsumiya et al, 2007) …”
Section: Systeminmentioning
confidence: 99%
See 1 more Smart Citation
“…B. rapa and S. lycopersicum (Takii Seed Corp., Kyoto, Japan) were used for each assay. The soybean-meal medium contained 10% (w/v) soybean meal (Honen soyalex, Honen Corp., Tokyo, Japan) [21,22]; the Luria-Bertani medium contained 10 g peptone, 5 g yeast extract, 5 g NaCl, and 20 g agar (pH 7.0) in 1 l H 2 O [23]; and the plant growth medium contained a mixture of 1 ml trace nutrient solution (…”
Section: Methodsmentioning
confidence: 99%
“…An alkaline protease from Bacillus circulans HA12 efficiently degrades soybean meal, and subsequently, it was shown that a variety of peptides are produced by the degradation . The RHPP (Gly‐Gly‐Ile‐Arg‐Ala‐Ala‐Pro‐Thr‐Gly‐Asn‐Glu‐Arg) present in the degraded soybean‐meal products (DSP) has root hair‐promoting activity . The RHPP promotes root hair differentiation by increasing the number of trichoblasts (root hair cells) in Brassica rapa .…”
Section: Introductionmentioning
confidence: 99%